Tendon bioreactor - Zubir, Nazira; Mat Noor, Nina Azurainie; Pushpanathan, Kalananthni (2016)
The drawbacks of surgery and grafts pertaining to the chronic tendon ailments or aging factor have led to the emergence of promising alternative, engineered tendon tissues. The engineered tissue is capable to mimic the physiological function of the native tissue. The fundamental requirements of a bioreactor system to generate engineered tendon tissues are the construct or scaffold, the cell as well as chemical and mechanical stimulation. The dynamic tendon bioreactor system with appropriate mechanical stimulation also mimics the dynamics of the in vivo environment for tendon maturation. Thus, in designing tendon bioreactor, the cyclic stretch and tensile strains are vital when considering the choice of mechanical stimulation to promote efficient cell differentiation. The parameters such as frequency, the duration and the strain applied can further fine tune to meet the design requirement. Nevertheless, the optimum function of the bioreactor also relies on the mass transport of the nutrients or the medium circulation. In this prototype design of the tendon bioreactor, the mechanical stimulation such as stretch are considered to provide uniform distribution of the medium throughout the construct. The gear principle is used to generate the stretch motion. The media intake and discharge will be controlled automatically. Temperature, carbon dioxide level and oxygen level are controlled hence no incubator is required in the design. The temperature inside the bioreactor will be maintained through the heat exchanger. The temperature and pH of the media in this prototype bioreactor will be monitored by their respective sensors.